2011
DOI: 10.1007/s00428-011-1045-6
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of UPIa, UPIb, UPII, and UPIIIa during urothelial carcinogenesis induced by N-butyl-N-(4-hydroxybutyl)nitrosamine in rats

Abstract: In normal urothelium, superficial umbrella cells express four major integral membrane proteins, uroplakins UPIa, UPIb, UPII, and UPIIIa, which compose urothelial plaques. In the apical plasma membrane, urothelial plaques form microridges. During neoplastic changes, microridges are replaced by microvilli, while uroplakin expression is retained. We correlated individual uroplakin expression with apical plasma membrane structure, cytokeratin 20 expression, and urothelial cell proliferation (Ki-67). Male Wistar ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
13
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 46 publications
(50 reference statements)
3
13
1
Order By: Relevance
“…Therefore it is important to know whether the total UPs are expressed in preneoplastic or neoplastic urothelium, and whether all the urothelial plaques contain all four UPs, specific pairs of UPs or only individual UPs. We showed recently that during urothelial carcinogenesis, the expression of UPII is diminished (Zupančič et al 2011). We showed here by immunohistochemical staining, however, that all four UPs are expressed in some, but none in other areas of preneoplastic urothelium.…”
Section: Discussioncontrasting
confidence: 63%
“…Therefore it is important to know whether the total UPs are expressed in preneoplastic or neoplastic urothelium, and whether all the urothelial plaques contain all four UPs, specific pairs of UPs or only individual UPs. We showed recently that during urothelial carcinogenesis, the expression of UPII is diminished (Zupančič et al 2011). We showed here by immunohistochemical staining, however, that all four UPs are expressed in some, but none in other areas of preneoplastic urothelium.…”
Section: Discussioncontrasting
confidence: 63%
“…For example, others have found that normal rat control urothelium displays CK20 immunoreactivity in all superficial cells with none in intermediate and basal cells. 34 In rats administered the urinary bladder carcinogen N-butyl-N-(4-hydroxybutyl)nitrosamine, hyperplasias Figure 5. o-Nitroanisole, 18 000 ppm, 15 months.…”
Section: Discussionmentioning
confidence: 99%
“…Previous experiments showed modification of uroplakin expression during chemically induced rat urinary bladder carcinogenesis. 23,34 Using the differentiation markers CK20 and UPIII, we tested the hypothesis that the ability of urothelium to terminally differentiate is progressively lost during tumor progression. As urinary bladder cancer is a common cancer in humans and one of the most expensive cancers to treat overall, 4 there is a need to identify similarities and differences between urinary bladder cancers in humans and those in rats, since rodents are important models in carcinogenicity testing.…”
mentioning
confidence: 99%
“…The Uroplakin 1A (UPK1A) gene belongs to the transmembrane 4 super family (TM4SF), also known as the tetraspanin family [7], [8]. The expression of UPK1A is known to be highly specific to normal urothelium [9], and can be observed in the normal genitourinary tract, uterus and prostate [10]. Recently, a study by Kar and colleagues [11] found that UPK1A can be used as a molecular biomarker and is a significant tumor suppressor in esophageal squamous cell carcinoma (ESCC), which demonstrated that UPK1A plays a role in inhibiting cell proliferation, clonogenicity, cell motility, and tumor formation.…”
Section: Introductionmentioning
confidence: 99%